On the Fourth Edition of A Dictionary of South African English - Gold, David L. (Lexikos, 1992)
Having reviewed the first and third editions of A Dictionary of South African English in earlier publications, the author examines the fourth edition. He suggests a number of improvements with respect to several aspects of the dictionary, ranging from superficial, though important, matters (like layout and typography) to the most difficult aspects of lexicography (definition and etymology). Keywords: abbreviation, acronym, afrikaans, american english, black english, british english, consultant vs. researcher, contrastive linguistics, corpus-delimitation, dictionary, dutch, english, entry head, etymology, graphic illustration, hebrew, jewish english, judezmo, letterword, lexicography, new netherland dutch, northeastern yiddish, prescriptivism, south african english, western yiddish, yiddish